The thermal tolerance of photosynthetic tissues: a global systematic review and agenda for future research. Issue 5 (3rd December 2020) - Geange, Sonya R.; Arnold, Pieter A.; Catling, Alexandra A.; Coast, Onoriode; Cook, Alicia M.; Gowland, Kelli M.; Leigh, Andrea; Notarnicola, Rocco F.; Posch, Bradley C.; Venn, Susanna E.; Zhu, Lingling; Nicotra, Adrienne B.
Summary: Understanding plant thermal tolerance is fundamental to predicting impacts of extreme temperature events that are increasing in frequency and intensity across the globe. Extremes, not averages, drive species evolution, determine survival and increase crop performance. To better prioritize agricultural and natural systems research, it is crucial to evaluate how researchers are assessing the capacity of plants to tolerate extreme events. We conducted a systematic review to determine how plant thermal tolerance research is distributed across wild and domesticated plants, growth forms and biomes, and to identify crucial knowledge gaps. Our review shows that most thermal tolerance research examines cold tolerance of cultivated species; c.  5% of articles consider both heat and cold tolerance. Plants of extreme environments are understudied, and techniques widely applied in cultivated systems are largely unused in natural systems. Lastly, we find that lack of standardized methods and metrics compromises the potential for mechanistic insight. Our review provides an entry point for those new to the methods used in plant thermal tolerance research and bridges often disparate ecological and agricultural perspectives for the more experienced. We present a considered agenda of thermal tolerance research priorities to stimulate efficient, reliable and repeatable research across the spectrum of plant thermal tolerance.